2015
DOI: 10.5433/1679-0359.2015v36n1p217
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical, laboratory, and electrophoretic profiles for diagnosis of malnutrition in hospitalized dogs

Abstract: Malnutrition is a major factor associated with increased rates of mortality and readmission, longer hospital stays, and greater health care spending. Recognizing malnourished or at-risk animals allows for nutritional intervention and improved prognosis. This study evaluated the association between clinical, laboratory, and electrophoretic variables and the nutritional status (NS) of hospitalized dogs in order to generate a profile of the sick dog and to facilitate the diagnosis of malnutrition. We divided 215 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…In 2015, a study evaluated the BMI of 215 hospitalized dogs and observed a reduction in values in patients with severe clinical malnutrition but not in patients with moderate or subclinical malnutrition; therefore, the authors suggested that a low BMI reinforces the diagnosis of malnutrition but does not allow its early identification (Fabretti et al, 2015). Another study evaluated the BMI and BCS of 30 Labrador retriever dogs and showed disagreement in the interpretation of these techniques in 46.7% of the cases (Gama et al, 2016).…”
Section: Underweight Suggestivementioning
confidence: 99%
See 4 more Smart Citations
“…In 2015, a study evaluated the BMI of 215 hospitalized dogs and observed a reduction in values in patients with severe clinical malnutrition but not in patients with moderate or subclinical malnutrition; therefore, the authors suggested that a low BMI reinforces the diagnosis of malnutrition but does not allow its early identification (Fabretti et al, 2015). Another study evaluated the BMI and BCS of 30 Labrador retriever dogs and showed disagreement in the interpretation of these techniques in 46.7% of the cases (Gama et al, 2016).…”
Section: Underweight Suggestivementioning
confidence: 99%
“…Another study evaluated the BMI and BCS of 30 Labrador retriever dogs and showed disagreement in the interpretation of these techniques in 46.7% of the cases (Gama et al, 2016). In summary, most studies show that the classification of NS based on BMI alone is not the best option because it does Clinical determination of the nutritional status of companion animals not reflect fat distribution and other factors, such as muscle or plasma volume, that affect this index directly (Muller et al, 2008;Fabretti et al, 2014Fabretti et al, , 2015Gama et al, 2016).…”
Section: Underweight Suggestivementioning
confidence: 99%
See 3 more Smart Citations